Static thyristor compensator with forced commutation and isolated neutral and scheme of its controlling - Пєтухов, Микола Васильович; Літковець, Сергій Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
In this work the configuration, principle of operation of static thyristor compensator with forced commutation and isolated neutral are considered, the integral indicators of its energy process and speed of operation for two management strategies of reactive power are determined. It is established, that the value of reactive power of compensator in the case of its voltage by the supply of rectangular shape is almost a linear function of the angle control of commuting thyristors for the considered management strategies, and the increase of the angle control of thyristor causes the decrease of the value of specific active power consumption, which is the criterion of economic efficiency of the compensator as a source of reactive power. At the defined values of angle control thyristors the value of specific active power consumption is less than the value of the basic variant of the same name, which corresponds sinusoidal supply of compensator that allows realizing power effective technologies management modes of its work. The designed the scheme of control of static thyristor compensator provides the proper speed of operation for reacting to rapid changes of reactive power, independent control of phase reactors of two adjacent phases, needed algorithm of switching commuting thyristors and microprocessor control of all elements of the system in real time to reduce the value of the specific active power consumption and, thus, to realize the concept of a global management energy processes in compensator.